Intellectual Humility and the Argument from Evil: A Reply to Zain Ali - Bishop, John (Religions, 2024)
This is a response to Zain Ali’s critique in this journal of our presentation of a ‘right relationship’ normatively relativised ‘logical’ Argument from Evil. Our argument aims to show that the existence of horrendous evils (as defined by Marilyn Adams) is incompatible with the existence of the personal omniGod (a person or personal being who is all-powerful, all-knowing, and perfectly good), given certain reasonable judgments about what a personal God’s perfect goodness would imply about the way God relates to those caught up in horrendous evils. We reply to Ali’s main criticism that our assumptions about divine goodness are unjustified, and show a lack of intellectual humility. We defend the claim that, if God is a person, then God’s goodness is moral goodness according to our best human theory of what that implies. We accept that God’s situation as creator and sustainer of all that exists may justify ‘divine exceptionalism’: God’s personal moral goodness may be consistent with ways of relating to others that would fall far short of perfection in human-to-human relationships. But in that case, we argue, intellectual humility may be better served by accepting that God is so exceptional that God should not be understood as a person at all, which is the prevailing Muslim view, as Ali himself acknowledges.